The effect of biogenic calcium phosphate nanoparticles on drought-stressed barley - Elsherif, Doaa E.; Safhi, Fatmah A.; El-Esawy, Mai A.; Mira, Mohammed M.; Al Aboud, Nora M.; Razzaky, Esraa O. (Frontiers in Plant Science, 2025)
Drought stress is one of abiotic stresses that significantly reduces agricultural yield annually. In response to drought, plants undergo several physiological and morphological changes like reduced transpiration and photosynthetic rate, disturbed osmotic adjustments, repressed root as well as shoot growth and overproduction of reactive oxygen species (ROS). In an experiment, a clay-sand mixture was placed in plastic pots containing barley seeds (Hordeum vulgare L., Giza 134), which were irrigated with 30% of the field capacity (FC). After one week, the pots were treated with different concentrations of biogenic calcium phosphate nanoparticles (CaPNPs) (25, 50 and 100 mg/L). Fourteen days later, the morpho-bio-physiological features were measured and documented. Applying 50 as well as 100 mg/L of CaPNPs on the well-watered leaves of barley plants increased shoot and root lengths, biomass, carbohydrates, non-enzymatic as well as enzymatic antioxidants, in addition to gene expression of superoxide dismutase (HvSOD) and catalase (HvCAT); such dosages mainly have been the optimal doses under normal conditions. Since calcium is a second messenger molecule, it can activate a variety of physiological signaling pathways when applied topically, mitigating the negative effects of drought stress on the development and metabolism of barley. Therefore, the application of CaPNPs yielded significant improvements across various plant functions despite drought stress conditions. Notably, there was an enhancement in growth parameters, osmo-protectants, and both cellular enzymatic and non-enzymatic antioxidants. At the molecular level, genes associated with betaine aldehyde dehydrogenase (HvBADH1), mitogen-activated protein kinases (HvMAPK3), showed provoked activity, particularly at a concentration of 25 mg/L. Furthermore, the treatment led to a decrease in ROS, as evidenced by reduced levels of malondialdehyde (MDA) and hydrogen peroxide. This reduction in ROS indicates an overall impediment of oxidative stress in the plants. Overall, the results of this study provide new insights into the molecular and physiological processes behind H. vulgare’s response to the optimal dose of biogenic CaPNPs, which is 50 and 100 mg/L in majority of the parameters in normal conditions and 25 mg/L under drought ones.